Gender Dysphoria – Prevalence and Co-Morbidities in an Irish Adult Population - Judge, Ciaran; O’Donovan, Claire; Callaghan, Grainne; Gaoatswe, Gadintshware; O’Shea, Donal (Frontiers in Endocrinology, 2014)
Introduction: Gender dysphoria is a condition in which there is a marked incongruence between an individual’s psychological perception of his/her sex and their biological phenotype. Gender Identity Disorder was officially renamed ‘Gender Dysphoria’ (GD) in the DSM-V in 2013. The prevalence and demographics of GD vary according to geographical location and have not been well documented in Ireland. Methods: We retrospectively reviewed medical records of 218 patients with suspected or confirmed GD referred to our endocrine service for consideration of hormonal therapy between 2005 and early 2014. We documented their demographics, clinical characteristics and treatment during the study period. Results: The prevalence of gender dysphoria in the Irish population was 1:10,154 MTF and 1:27,668 FTM, similar to reported figures in Western Europe. 159 of the patients were male-to-female (MTF) and 59 were female-to-male (FTM), accounting for 72.9% and 27.1% of the cohort respectively. The rate of referral has increased year-on-year, with 55 patients referred in 2013 versus 6 in 2005. Mean ages were 32.6y (MTF) and 32.2y (FTM). 22 patients were married and 41 had children, with 2 others having pregnant partners. 37.6% were referred by a psychologist, with the remainder evenly divided between GPs and psychiatric services. There were low rates of coexistent medical illness although psychiatric conditions were more prevalent, depression being a factor in 34.4% of patients. 5.9% of patients did not attend a mental health professional. 74.3% are currently on hormonal therapy, and 9.17% have had gender reassignment surgery (GRS). Regret following hormonal or surgical treatment was in line with other Western European countries (1.83%). Conclusion: The incidence of diagnosis and referral of GD in Ireland is increasing. This brings with it multiple social, health and financial implications. Clear and accessible treatment pathways supported by mental health professionals is essential.